Análise discursiva da imagem da mulher operária da Zona Franca de Manaus - Marcondes Cabral de Abreu (Universidade Federal do Amazonas, 2016)
This work seeks to analyze, in agreement with the assumptions of discourse analysis of the French headquarters, the discursive functioning of the newspaper Jornal do Comercio and Critique. We intend to investigate how these newspaper are dealing with the image of women working in the Manaus Free Zone, especially on the internacional women's week, during the years 2006 to 2010.